1984
DOI: 10.1002/ijc.2910340607
|View full text |Cite
|
Sign up to set email alerts
|

Follow‐up study of hbs ag‐positive blood donors with special reference to effect of drinking and smoking on development of liver cancer

Abstract: In order to confirm the close association between chronic hepatitis B virus (HBV) infection and primary hepatocellular carcinoma (PHC) in Japan, 8,646 male hepatitis B surface antigen (HBs Ag)-positive blood donors (GPT less than or equal to 35 Karmen units) were followed up. Twenty liver cancer cases were observed during the follow-up period (average 6.2 years), the expected number calculated on the basis of age-specific incidence rates among the general population being 3.03. Therefore, the observed to expec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
41
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(42 citation statements)
references
References 10 publications
0
41
1
Order By: Relevance
“…In Japan, where HCC has been related mainly to HCV infection, an excess mortality due to HCC and LC in HBV carriers was also found. [10][11][12][13][14][15] In China and Taiwan, where HCC has been related mostly to HBV, the estimated risks for HCC among men vary between 7 and 103, [3][4][5][6][7][8][9] showing higher risks than those in other geographical areas. The higher risk of death from liver disease found in South East Asia has also been reported in Western studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In Japan, where HCC has been related mainly to HCV infection, an excess mortality due to HCC and LC in HBV carriers was also found. [10][11][12][13][14][15] In China and Taiwan, where HCC has been related mostly to HBV, the estimated risks for HCC among men vary between 7 and 103, [3][4][5][6][7][8][9] showing higher risks than those in other geographical areas. The higher risk of death from liver disease found in South East Asia has also been reported in Western studies.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Most of these studies have been carried out in Asian countries (4 in China, [3][4][5][6] 2 in Taiwan 7-9 and 6 in Japan [10][11][12][13][14][15] ); 4 in Western countries (2 in the US, 16,17 1 in the UK 18,19 and 1 in 20 )…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A longitudinal study of hepatitis B surface antigenepositive healthy blood donors tested in Japan between 1972 and 1975 found that alcohol consumption greater than 27 g/day (duration of alcohol use not stated) was associated with more than a fivefold increase in the relative risk for development of HCC (Oshima et al, 1984). A study that compared two case series suggested that patients with HCC caused by chronic HBV and chronic alcohol are approximately 10 years younger than patients with HCC caused by chronic HBV alone (Ohnishi et al, 1982;Pereira et al, 1994).…”
Section: Introductionmentioning
confidence: 99%